Does graft hemodynamics affect the risk of hepatocellular carcinoma recurrence after liver transplantation?. Issue 8 (24th June 2020) - Matsushima, Hajime; Acevedo‐Moreno, Lou‐Anne; Sasaki, Kazunari; Fujiki, Masato; Kwon, Choon Hyuck David; Uso, Teresa Diago; D'Amico, Giuseppe; Aucejo, Federico; Eghtesad, Bijan; Miller, Charles; Quintini, Cristiano; Hashimoto, Koji
Abstract: Although experimental studies have reported that hepatic ischemia‐reperfusion injury promotes tumor growth and metastases, the impact of graft hemodynamics on the recurrence of hepatocellular carcinoma (HCC) after liver transplantation (LT) is unclear. To investigate the association between graft hemodynamics and HCC recurrence after LT, we conducted a retrospective analysis of 279 patients who underwent LT for HCC. Graft hemodynamics including portal vein flow (PVF), hepatic artery flow (HAF), and total hepatic flow (THF) was analyzed as a predictor of HCC recurrence, using competing risk regression analyses. The cutoff values of PVF, HAF, and THF were set at the lower quartile of distribution. A cumulative recurrence curve demonstrated that low THF (<1511 mL/min, P  = .005) was significantly associated with increased recurrence, whereas neither low PVF (<1230 mL/min, P  = .150) nor low HAF (<164 mL/min, P  = .110) was significant. On multivariate analysis, outside Milan criteria (sub‐hazard ratio [SHR] = 3.742; P  < .001), microvascular invasion (SHR = 3.698; P  < .001), and low THF (SHR = 2.359; P  = .010) were independently associated with increased HCC recurrence. In conclusion, our findings suggest that graft hemodynamics may play an important role in HCC recurrence after LT.